Molecular Mechanisms of Photoadaptation of Photosystem I Supercomplex from an Evolutionary Cyanobacterial/Algal Intermediate . Issue 2 (6th February 2018) - Haniewicz, Patrycja; Abram, Mateusz; Nosek, Luká¡; Kirkpatrick, Joanna; El-Mohsnawy, Eithar; Olmos, Julian D. Janna; Kouřil, Roman; Kargul, Joanna M.
Abstract : Zeaxanthin accumulation and antenna remodeling protect the extremophilic red alga Cyanidioschyzon merolae PSI supercomplex from light stress. Abstract: The monomeric photosystem I-light-harvesting antenna complex I (PSI-LHCI) supercomplex from the extremophilic red alga Cyanidioschyzon merolae represents an intermediate evolutionary link between the cyanobacterial PSI reaction center and its green algal/higher plant counterpart. We show that the C. merolae PSI-LHCI supercomplex is characterized by robustness in various extreme conditions. By a combination of biochemical, spectroscopic, mass spectrometry, and electron microscopy/single particle analyses, we dissected three molecular mechanisms underlying the inherent robustness of the C. merolae PSI-LHCI supercomplex: (1) the accumulation of photoprotective zeaxanthin in the LHCI antenna and the PSI reaction center; (2) structural remodeling of the LHCI antenna and adjustment of the effective absorption cross section; and (3) dynamic readjustment of the stoichiometry of the two PSI-LHCI isomers and changes in the oligomeric state of the PSI-LHCI supercomplex, accompanied by dissociation of the PsaK core subunit. We show that the largest low light-treated C. merolae PSI-LHCI supercomplex can bind up to eight Lhcr antenna subunits, which are organized as two rows on the PsaF/PsaJ side of the core complex. Under our experimental conditions, we found no evidence of functional coupling of the phycobilisomes with the PSI-LHCI supercomplex purified from various light conditions, suggesting that the putative association of this antenna with the PSI supercomplex is absent or may be lost during the purification procedure.